If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -3x = 6x + 17 Reorder the terms: 65 + -3x = 17 + 6x Solving 65 + -3x = 17 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 65 + -3x + -6x = 17 + 6x + -6x Combine like terms: -3x + -6x = -9x 65 + -9x = 17 + 6x + -6x Combine like terms: 6x + -6x = 0 65 + -9x = 17 + 0 65 + -9x = 17 Add '-65' to each side of the equation. 65 + -65 + -9x = 17 + -65 Combine like terms: 65 + -65 = 0 0 + -9x = 17 + -65 -9x = 17 + -65 Combine like terms: 17 + -65 = -48 -9x = -48 Divide each side by '-9'. x = 5.333333333 Simplifying x = 5.333333333
| 99-7a=2a | | 3(4x+1)=5x-6x | | 0=x^2+25 | | 9x-15/4=2x+3 | | 5y^3-80y+2y^2-32=0 | | 5x+42=8x-109 | | 3x+8=72-5x | | smokvrya=blg | | x²-3x+2=0 | | 10+2x/3=4 | | 1616.9=1.8C+32 | | c^2+13c+12=0 | | 3x+3=-5x-12 | | h=-16t^2-13t+150 | | 81x^2=81 | | smokwdvrya=blg | | g^2-22g+40=0 | | 3x+3-5x=12-6x+7 | | 1-6x=9-6x | | X^2+25=9 | | 25-6x=3x+20 | | p^2+21p+99=0 | | 4a=20+2a | | 9+3z-6=9z+12-3z | | -1-6x=9-6x | | 10-x=90-38x | | j^2+13j+30=0 | | 2x+14=2x-14 | | 3-2g=9 | | h=16t^2-12t+140 | | m^2+14m+48=0 | | 2x+3/5=x-4/2 |